Minority Shareholders : What Works to Protect Shareholder Rights? - Capaul, Mierta (World Bank, Washington, DC, 2012)
The World Bank's assessments of corporate governance practices in 25 countries across five continents have revealed a general commitment to comply with international principles. But the necessary legal changes are slow and subject to political compromise. Moreover, most countries have a poor track record in enforcing existing laws and regulations. Expropriation of minority shareholders continues to be a problem around the world. The corporate governance assessments show that choice can facilitate reform. Allowing different models of corporate governance to coexist permits investors with varying risk profiles to choose the appropriate market and company to invest in and allows market forces to pick the winners. When companies have the choice of listing their shares on a stock market segment with stricter corporate governance rules or of complying with a code of best practice, they can use this option to signal to investors that they are different. While establishing a corporate governance market segment appears to be an attractive option only for middle-income countries, codes of best practice seem to be important regardless of a country's level of development.